The Economy of Communities around Forest Area in Dairi Regency - Posma Charli Parlindungan Silaen; Agus Purwoko; Siddik Thoha (Budapest International Research and Critics University, 2020)
The aim of the study is to find out the economy of communities around forest area in Dairi Regency. The result of the study shows that The direction of utilization of the Dairi Regency forest area that can be developed to improve the community's economy through social forestry permits in each function of protected forest area of ± 20,138.70 ha. The area of limited production forest that can be utilized is ± 14,068.86 ha. The area of production forest is ± 4,974.84 ha. The area of conservation forest of Gunung Leuser National Park which will be utilized ± 86.24 ha is located in Tanah Pinem District. The area of conservation forest of Sicike-Cike Nature Tourism Park which will be utilized ± 0.16 ha is located in Sitinjo District. The area covered by water in the forest area that can be utilized is ± 127.31 ha. The total area of forest area to be utilized based on the function of the area and its area is ± 39,396.10 ha.